Reliability and Validity of Turkish Myasthenia Gravis-Activities of Daily Living Scale. (April 2021) - Karanfil, Ecem; Salcı, Yeliz; Fil-Balkan, Ayla; Bekircan-Kurt, Can Ebru; Erdem Özdamar, Sevim; Armutlu, Kadriye
Linguistic, reliable, and valid secondary efficacy measures are important in clinical settings and studies. The aim of the study is to report test–retest reliability and construct validity of Turkish version of Myasthenia Gravis-Activities of Daily Living Scale (MG-ADL-T) in Myasthenia Gravis (MG) patients. Fifty-two ocular and generalized individuals with MG, applying to rehabilitation center, were included in the study. MG-ADL-T, MG quality-of-life questionnaire (MG-QoL), MG composite (MGC), quantitative MG score (QMGS), and pulmonary function test were administered. Reliability was assessed with intraclass correlation coefficient (ICC) and Cronbach's alpha. Spearman correlation test and receiver operating characteristic (ROC) analysis were performed for construct validity. MG-ADL-T had fair internal consistency (Cronbach's α = .67), excellent test–retest reliability (ICC = 0.96) and moderate construct validity (MG-QoL, r = 0.59; QMGS, r = .58; MGC, r = .68). MG-ADL, a unique scale that evaluates activities of daily living (ADL), has good test–retest reliability and construct validity in Turkish MG patients.